P483 Home oxygen referral in premature neonates born in UMHL over two years period. (June 2019) - Ijaz, Aisha; Bakar, Mohammed Abu; Khan, Rizwan; Raza, Ghulam
Abstract : Background: Bronchopulmonary dysplasia(BPD) has been a challenging condition for neonatologists(1). Prematurely born infants who had BPD may require supplementary oxygen at home for many months(2). Objectives: To determine the number of premature babies discharged on home oxygen over two years period in UMHL and to confirm about average gestation age at which babies were self ventilating in air. Methodology: Retrospective data of 38 babies equal to or less than 29 weeks of gestation was collected, born in UMHL from February 2016 to February 2018. Different variables were studied including Gestation at birth, Birth weight, Date of admission, Date of discharge, Gestation for self ventilation in air, Gestation of home oxygen referral and gestation at discharge. Management of Chronic Lung Disease in the form of steroids, diuretics, patent ductus arteriosus(PDA) treatment and number of blood transfusions were also looked upon. Results: Total 38 babies born in UMHL from February 2016 to February 2018, equal to or less than 29 weeks of gestation. 26%(n=10) babies were excluded from the study including 21%(n=8) babies died, 3%(n=1) chart missing and 3%(n=1) baby lost follow up. 71%(n=20) were born in the gestation range of 26 to 28 weeks and 70%(n=19) were between birth weight of 750 grams to 1250 grams. 59%(n=16) babies were self ventilating in air between 31 to 35 weeks of gestation compared to 11%(n=3) who took over 41 weeks of corrected gestational age. 4%(n=1) babies were not able to wean off from oxygen over two years period. 29%(n=8) of the babies didn't need any intervention (Diuretics, Steroids, PDA management, Blood transfusion) during their stay in NICU while 29%(n=8) needed just one intervention. 43%(n=12) of the babies needed two or more interventions to achieve self ventilation in air. Conclusion: Only one baby out of total 28 was discharged on home oxygen over two years period and most of the babies were able to achieve self ventilation in air between 31st to 35th weeks of gestation. References: Colby L. Day, Rita M. Ryan. Bronchopulmonary dysplasia: new becomes old again! Pediatric Research 2017;81:210–213 Greenough A, Long-term respiratory consequences of premature birth at less than 32 weeks of gestation, Early Human Development 2013 Oct;89Suppl 2:S25–7